The Thermalization of Quantum Systems - Reichl, L.E. (Journal of Applied Nonlinear Dynamics, 2026)
The fact that the Earth is becoming hotter poses an existential threat for some life forms on Earth. But what is heat? Surprisingly, the answer to this question is not completely clear. We here explore the history of the quest to understand the microscopic mechanical origins of heat. We also describe what is presently known about the dynamical structure of phase space when heat is present.